2009
DOI: 10.1095/biolreprod.109.078816
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Mouse Sperm Hyaluronidases, HYAL5 and SPAM1, in Fertilization1

Abstract: Although sperm entry into the oocyte-cumulus complex and subsequent sperm penetration through the cumulus matrix to reach the oocyte zona pellucida are essential for mammalian fertilization, the molecular mechanism remains controversial. Previously, we have shown that mouse sperm lacking SPAM1 are capable of penetrating the cumulus matrix despite a delayed dispersal of cumulus cells. We also have identified another sperm hyaluronidase, HYAL5, as a candidate enzyme involved in sperm penetration through the cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 33 publications
8
72
1
Order By: Relevance
“…However, the goal of the exchange between oocytes and sperm is not to supply spermatozoa in CD9 tetraspanin. In fact, as described previously (Kimura et al 2009, Ito et al 2010 and confirmed here, the CD9 tetraspanin is also expressed on mouse sperm at a high level and is localised on the equatorial segment after acrosome reaction. This result shows that CD9 is mostly detected at the surface of the fertilising sperm at…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the goal of the exchange between oocytes and sperm is not to supply spermatozoa in CD9 tetraspanin. In fact, as described previously (Kimura et al 2009, Ito et al 2010 and confirmed here, the CD9 tetraspanin is also expressed on mouse sperm at a high level and is localised on the equatorial segment after acrosome reaction. This result shows that CD9 is mostly detected at the surface of the fertilising sperm at…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to what has been initially described (Chen et al 1999, Li et al 2004, spermatozoa do also express CD9 tetraspanin, as recently reported (Kimura et al 2009, Ito et al 2010 and as confirmed here. Indeed, we observed the presence of CD9 tetraspanin on cauda epididymal mature sperm.…”
Section: Wb Analysis Of Mouse Spermsupporting
confidence: 70%
“…It is the hydrolytic enzymes released following the AR that ensure sperms to disperse the cumulus mass and reach the zona layer (Talbot, 1985;Yanagimachi, 1988). Unfortunately, this hypothesis is challenged by the observation that the expression of hydrolytic enzymes thought to facilitate sperm penetration of the cumulus, PH-20 and Hyal5, were found on the surface of sperm membrane but not within the acrosome (Lin et al, 1994;Kim et al, 2005;Kimura et al, 2009), which means sperm do not necessarily undergo AR to release hydrolytic enzymes when passing through the cumulus layer. Recent results obtained from PH-20 null mice have revealed that mouse sperm lacking PH-20 are still fertile with only delayed penetration through the cumulus (Baba et al, 2002), while sperm lacking both PH-20 and Hyal5 have not yet been studied.…”
Section: Status Of Sperm Acrosome In the Cumulus: The Controversymentioning
confidence: 99%
“…Mouse epididymal sperm contain at least two hyaluronidases, SPAM1 and HYAL5, glycosylphosphatidylinositol (GPI)-anchored on the plasma and/or acrosomal membranes [8][9][10][11]. We previously demonstrated that SPAM1 is localized only on the plasma membrane of sperm and that acrosome-reacted sperm still retain approximately half of SPAM1 [9].…”
mentioning
confidence: 99%
“…On the basis of the subcellular distribution, both HYAL5 and SPAM1 on the plasma membrane may be involved in sperm penetration through the cumulus matrix, and acrosomal HYAL5 released by the acrosome reaction may play an important role in the local hyaluronan hydrolysis near or on the ZP surface to enable the proximal region of the sperm tail to move freely [10]. Inconsistent with these possibilities, male mice lacking either one of these two hyaluronidases (Spam1 -/-or Hyal5 -/-) have been shown to be fully fertile [9,11], providing evidence that neither SPAM1 nor HYAL5 is essential for fertilization in the mouse. However, in vitro fertilization (IVF) assays have revealed that Spam1 -/-sperm are distinguished from wild-type and Hyal5 -/-sperm by significant delays in entering the OCC, dispersing cumulus cells from the OCC and traversing the cumulus matrix to reach the ZP [11].…”
mentioning
confidence: 99%